A New Approach to estimate the Wage Returns to Work-related Training - Edwin Leuven; Hessel Oosterbeek (Tinbergen Institute, 2002)
This paper proposes a new approach to identify the wage effects of training.The idea is to narrow down the comparison group by only taking into consideration theworkers who wanted to participate in training but did not do so because of some randomevent. The point estimate of the return to training consistently drops when restrictingthe comparison group this way. While the OLS estimate of the return to training participationis significantly positive, this is no longer the case when we use the new comparisongroup. This outcome suggests that a large share of what is usually interpreted as returnsto training is actually the return to some unobservable characteristic.
Keywords: 330; Bildungsertrag; Weiterbildung; Mikroökonometrie; Schätzung; Theorie; Niederlande